Graphitic Carbon Materials for Advanced Sodium‐Ion Batteries. Issue 4 (5th September 2018) - Xu, Zheng‐Long; Park, Jooha; Yoon, Gabin; Kim, Haegyeom; Kang, Kisuk
Abstract: Lithium‐ion batteries (LIBs) have dominated the energy storage market for more than two decades; however, the quest for lower‐cost battery alternatives is rapidly expanding, especially for large‐scale applications. Sodium‐ion batteries (SIBs) have recently experienced an impressive resurgence owing to the earth's abundance of sodium resources and the similar electrochemistry of SIBs and the well‐established LIBs. Nonetheless, whereas cost‐effective and reliable graphite anodes have served as a cornerstone in current LIB technology, one of the major limitations of SIBs has been the inability to exploit graphite as an electrode because of its negligible sodium storage capability. Recently, however, clear progress has been made in preparing high‐performance graphitic carbon anodes for SIBs with new findings on the mechanisms of sodium storage. Herein, this paper aims to review the progress made in understanding the sodium storage mechanisms in graphitic carbon materials and comprehensively summarize the start‐of‐the‐art achievements by surveying the correlations among the type of graphitic material, microstructure, sodium storage mechanisms, and electrochemical performance in SIBs. In addition, perspectives related to practical applications, including the electrolyte, coulombic efficiency, and applicability in sodium‐ion full cells, are also presented. Abstract : Graphitic carbon materials are promising anodes for the burgeoning sodium‐ion battery (SIB) technology. An overview of the state‐of‐the‐art achievements in graphitic carbon anode materials for SIBs is summarized. New findings of sodium storage mechanisms are highlighted, associated with discussion of the correlation between microstructures and electrochemical performance. Perspectives for applicable SIBs are also presented.